Kinesiology Tape in Comparison with Oral Diclofenac Sodium in Reducing Swelling After Surgical Removal of Lower Wisdom Teeth - Issam Abdullah Mohammed; Ziad H. Delemi (University of Mosul, College of Dentistry, 2019)
The aims of the proposed research are to estimate the usefulness of two manners in reducing puffiness following extraction of third molar teeth. Materials and Methods: This study included 30 cases had unerupted lower third molar teeth of diverse surgical complexity. Kinesiology tape applied for 7 days after that removed or Diclofenac Na+ (Voltarin) 50mg tablet were given to the case group post operatively, three periods each day for seven days. Edema was assessed by a ribbon gauge method. Assessments were done on first day of surgical management and on seventy-two hours and seven days afterward. Results: There was a significant difference were recognized statistically for edema values between two treatment set on the 1st, 3rd and 7th day subsequent to surgical work. Conclusions: The use of Kinesiology tape was nearly with a same effectiveness with Voltarin tablets in dropping the edema, Kinesiology tape becomes able to be seen to at hand a beneficial result as an additional medicine in medically threatened patient like elevated blood pressure, chronic respiratory diseases, expectant females, gastric or duodenal ulcer, any contraindication of taking NSAIDs that is prescribed officially for decreasing ache, edema following to third molar teeth surgical interventions. Keywords: Kinesiology tape, Diclofenac, wisdom teeth removal.